Peran agama dalam memperkuat/membentuk identitas nasional - Sholihah, Imroatus (Maliki Interdisciplinary Journal, 2025)
The role of religion in strengthening and shaping national identity in Indonesia is very important given that Indonesia is a country with diverse religions, tribes, cultures, and languages. Religion also serves as a unifier amid the nation’s diverse cultures and tribes, where religious major day celebrations are often celebrated together as a form of togetherness. In addition, religion reinforces ethical values such as tolerance, justice, and compassion, which underpin the peaceful social life of Indonesians. During the independence struggle, religion contributed to the fighting spirit that inspired the nation to achieve independence. In the social context, religion plays an important role in maintaining harmony among religious people, teaching mutual respect, and strengthening the spirit of nationalism.